Rituximab in combination with corticosteroids for the treatment of anti-neutrophil cytoplasmic antibody-associated vasculitis: a NICE single technology appraisal. - Latimer, N; Carroll, C; Wong, R; Tappenden, P; Venning, M; Luqmani, R (2014)
As part of its single technology appraisal (STA) process, the National Institute for Health and Care Excellence (NICE) invited the manufacturer of rituximab (Roche Products) to submit evidence of the clinical and cost effectiveness of rituximab in combination with corticosteroids for treatment of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). The School of Health and Related Research Technology Appraisal Group at the University of Sheffield was commissioned to act as the independent Evidence Review Group (ERG). The ERG produced a critical review of the evidence for the clinical and cost effectiveness of the technology, based upon the manufacturer's submission to NICE. The evidence was derived mainly from a double-blind, phase III, placebo-controlled trial of rituximab in patients with new or relapsed 'severe' AAV, which compared a rituximab treatment regimen with an oral cyclophosphamide treatment regimen. Intravenous cyclophosphamide is also commonly used but was not included in the pivotal trial. The evidence showed that rituximab is noninferior to oral cyclophosphamide in terms of induction of remission in adults with AAV and de novo disease, and is superior to oral cyclophosphamide in terms of remission in adults who have relapsed once on cyclophosphamide. The ERG concluded that the results of the manufacturer's economic evaluation could not be considered robust, because of errors and because the full range of relevant treatment sequences were not modelled. The ERG amended the manufacturer's model and demonstrated that rituximab was likely to represent a cost-effective addition to the treatment sequence if given after cyclophosphamide treatment.